Distinct Roles for Bacterial and Fungal Communities During the Curing of Vanilla - Xu, Fei; Chen, Yonggan; Cai, Yingying; Gu, Fenglin; An, Kejing (Frontiers in Microbiology, 2020)
Vanilla produces aroma after curing. There were a few reports about the possible involvement of microorganisms during the curing process. Bacterial and fungal community was analyzed to explore the distinct roles. Alpha diversity analysis indicated that the abundance and diversity of microorganisms did not increase regularly as the curing progressed. Weighted and unweighted principal coordinates analysis (PCoA) showed that the fungal community of blanching beans was significantly different from those of the vanilla beans of other stages, respectively. Bacillus and Aspergillus were the dominant genus during the curing process. Correlation analysis indicated that the bacterial and fungal structure was positively related to the vanillin formation, respectively. The study was conducive to reveal the formation of flavor components and the biosynthesis of vanillin. Furthermore, it proposed the possible curing methods of regulating the bacterial and fungal community to increase vanillin formation.